2019
DOI: 10.29333/iji.2019.12157a
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Students and Faculty Staff on the Role of Constructive Feedback

Abstract: One of the most effective ways for teachers to ensure that their students have obtained the specified learning outcomes is to provide them with constructive feedback. If students are not given the optimal feedback and are not asked to re-do the work, teachers will not know whether the educational goals have been met. This study aimed to investigate whether Bahrain Teachers College students receive constructive feedback from their teachers. It explored both teachers' and students' perceptions about the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 10 publications
(12 reference statements)
1
21
0
Order By: Relevance
“…In this study, however, most teachers and students did not see that time or any other reason could be deemed a barrier to not providing constructive feedback. [ 15 ] In another qualitative study titled “Barriers and Facilitators to Effective Feedback”[ 16 ] conducted on multispecialty resident focus groups, the residents described the constraint between managing the busy pace of clinical work and making time for feedback, thus limiting the availability of feedback. In medical education context, feedback must be an integral constituent of the learning process and the perceived barriers can be overcome through proper planning and orientation of both students and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, however, most teachers and students did not see that time or any other reason could be deemed a barrier to not providing constructive feedback. [ 15 ] In another qualitative study titled “Barriers and Facilitators to Effective Feedback”[ 16 ] conducted on multispecialty resident focus groups, the residents described the constraint between managing the busy pace of clinical work and making time for feedback, thus limiting the availability of feedback. In medical education context, feedback must be an integral constituent of the learning process and the perceived barriers can be overcome through proper planning and orientation of both students and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings of a recent study by Bhattacharyya where time and work constraints were identified as major barriers to giving effective feedback 19 . However, in a study by Al-Hattami most teachers and students did not see that time, feasibility, amotivation or uncaring attitude towards students could be deemed a barrier to not providing constructive feedback 20 . Participants also shared hearsay about problems arising out of interaction with students of opposite genders, which contributed to their hesitation.…”
Section: Discussionmentioning
confidence: 97%
“…This means that assessment should not only focus on weaknesses but also point out the strengths of the learners as part of motivating them. The practice of giving constructive and corrective feedback is crucial in terms of sustaining the learners' motivation and effort towards learning (Al-Hattami, 2019).…”
Section: Found It Helpful To Change the Members Of The Groups From Time To Time (Teacher 7)mentioning
confidence: 99%
“…Flexibility grouping on the other hand enables better differentiation (McKeen, 2019) and also allows teachers to tailor mathematics instruction such that they meet the needs of diverse learners. The practice of providing the constructive and empowering corrective feedback is crucial in terms of sustain motivation and effort (Al-Hattami, 2019). This should be the type of feedback that not only focus on making learners aware of their mistakes but also shows areas in which they are doing well.…”
Section: Offer the Alternatives For Sustaining Effort And Persistencementioning
confidence: 99%